Characterization of metabolites in infiltrating gliomas using ex vivo1H high‐resolution magic angle spinning spectroscopy. (5th March 2014) - Elkhaled, Adam; Jalbert, Llewellyn; Constantin, Alexandra; Yoshihara, Hikari A. I.; Phillips, Joanna J.; Molinaro, Annette M.; Chang, Susan M.; Nelson, Sarah J.
<x xml:space="preserve">Abstract</x> Gliomas are routinely graded according to histopathological criteria established by the World Health Organization. Although this classification can be used to understand some of the variance in the clinical outcome of patients, there is still substantial heterogeneity within and between lesions of the same grade. This study evaluated image‐guided tissue samples acquired from a large cohort of patients presenting with either new or recurrent gliomas of grades II–IV using ex vivo proton high‐resolution magic angle spinning spectroscopy. The quantification of metabolite levels revealed several discrete profiles associated with primary glioma subtypes, as well as secondary subtypes that had undergone transformation to a higher grade at the time of recurrence. Statistical modeling further demonstrated that these metabolomic profiles could be differentially classified with respect to pathological grading and inter‐grade conversions. Importantly, the myo‐inositol to total choline index allowed for a separation of recurrent low‐grade gliomas on different pathological trajectories, the heightened ratio of phosphocholine to glycerophosphocholine uniformly characterized several forms of glioblastoma multiforme, and the onco‐metabolite D‐2‐hydroxyglutarate was shown to help distinguish secondary from primary grade IV glioma, as well as grade II and III from grade IV glioma. These data provide evidence that metabolite levels are of interest in the assessment of both intra‐grade and intra‐lesional malignancy. Such information could be used to enhance the diagnostic specificity of in vivo spectroscopy and to aid in the selection of the most appropriate therapy for individual patients. © 2014 The Authors. NMR in Biomedicine published by John Wiley & Sons, Ltd.